Plnění emisních norem u traktorových motorů - Vaško, Roman (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2012)
Předkládaná bakalářská práce se zabývá emisními normami traktorových motorů. V posledních letech dochází obecně k jejich zpřísnění. Úvodní pasáž práce je věnována popisu konkrétních škodlivin, které jsou exhalovány do ovzduší. Druhá část práce se zabývá nově zaváděnými normami Tier 4i (Stage IV). Technologie úprav motorů pro splnění nových předpisů jsou předmětem třetí části. Poslední kapitoly se zabývají přehledem největších výrobců traktorů, včetně tuzemského výrobce Zetor a jejich přístupu k problematice emisí.

This bachelor’s thesis deals with the emission standards of tractor engines. There is a tightening of standards in recent year generally. The former part of the thesis contains description of specific pollutants that are exhaled into the air. The second part is focused on newly presented Tier 4i standards (Stage IV). The third part includes technologies, which provide engines to meet new regulations. The last chapters deal with an overview of the largest manufacturers of tractors, including Zetor, and their approach to emissions.
Emission Levels for Tractor Engines
Keywords: Emise traktorových motorů; emisní složky; emisní limity; Tier; Stage; technologie SCR; SCR katalyzátor; močovina; roztok AdBlue; CEGR + DPF; výfukové filtry; Tier 4i; Tier 4 konečná verze; Stage IV.; Emission standards for mobile nonroad diesel engines; emission parts; emission limits; Tier; Stage; SCR technology; SCR catalytic converter; urea; AdBlue solution; CEGR + DPF; exhaust filters; Tier 4i; Tier 4 Final; Stage IV.